Surgical management of anterior clinoidal meningiomas: consensus statement on behalf of the EANS skull base section - Starnoni, D; Tuleasca, C; Giammattei, L; Cossu, G; Bruneau, M; Berhouma, M; Cornelius, J F; Cavallo, L; Froelich, S; Jouanneau, E; Meling, T R; Paraskevopoulos, D; et al. (Acta neurochirurgica, 2021)
BACKGROUND: The optimal management of clinoidal meningiomas (CMs) continues to be debated. METHODS: We constituted a task force comprising the members of the EANS skull base committee along with international experts to derive recommendations for the management of these tumors. The data from the literature along with contemporary practice patterns were discussed within the task force to generate consensual recommendations. RESULTS AND CONCLUSION: This article represents the consensus opinion of the task force regarding pre-operative evaluations, patient's counselling, surgical classification, and optimal surgical strategy. Although this analysis yielded only Class B evidence and expert opinions, it should guide practitioners in the management of patients with clinoidal meningiomas and might form the basis for future clinical trials.
Keywords: Meningeal Neoplasms; meningeom; neurochirurgické výkony; baze lební; Consensus; Skull Base; lidé; retrospektivní studie; Meningioma; Neurosurgical Procedures; Retrospective Studies; konsensus; meningeální nádory; Humans